2021
DOI: 10.1177/10598405211003303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nurse-Led Asthma Intervention on Child Health Outcomes: A Scoping Review

Abstract: Given the leading role school nurses occupy within the school setting, they are often the most suited health care professionals to lead asthma programs. However, most school-based asthma programs have been conducted by researchers outside the school setting. Thus, we aim to determine what is currently known about the type of school nurse-led asthma intervention programs and their impact on children’s asthma-related outcomes. This article describes published literature on school nurse-led asthma intervention pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
5
9
0
Order By: Relevance
“…This shows that the nursing intervention not only helps in preventing asthma related emergencies and exacerbations but also significantly improves the QoL of the children. These findings were also in line with the previous review findings (Isik et al, 2019; Kindi et al, 2021). The synthesis of these review findings demonstrated the importance of using nurse‐led interventions in any form, that is, hospital based, web based, community based or in combination of these modes of intervention focusing on the approaches to asthma control approaches meeting the children' needs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This shows that the nursing intervention not only helps in preventing asthma related emergencies and exacerbations but also significantly improves the QoL of the children. These findings were also in line with the previous review findings (Isik et al, 2019; Kindi et al, 2021). The synthesis of these review findings demonstrated the importance of using nurse‐led interventions in any form, that is, hospital based, web based, community based or in combination of these modes of intervention focusing on the approaches to asthma control approaches meeting the children' needs.…”
Section: Discussionsupporting
confidence: 93%
“…shows that the nursing intervention not only helps in preventing asthma related emergencies and exacerbations but also significantly improves the QoL of the children. These findings were also in line with the previous review findings (Isik et al, 2019;Kindi et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some schools are experimenting with the use of Telemedicine or video phone calls as ways to view a student’s inhaler technique when a school nurse is not in the building. Others are providing opportunities for students to view videos demonstrating proper inhaler technique (Al Kindi et al, 2021). While these cannot replace in-person care, they do offer some opportunities to improve students’ inhaler technique.…”
Section: Newer Proceduresmentioning
confidence: 99%
“…In another study of the Easy Breathing for Schools program, school nurses assessed asthma risk and asthma control, provided asthma education, and reviewed medication therapy using a pediatrician communication tool and enrolled children experienced a 25% decrease in school absences as compared to those not enrolled in this program [26]. Such school-nurse led strategies have great potential to improve asthma outcomes [27], and future directions of this work should consider how schools without full-time school nurses could participate in such approaches and whether existing school nurses would accept these types of responsibilities as part of their routine practice, outside of a research context.…”
Section: Introductionmentioning
confidence: 99%